Desempenho agronômico e digestibilidade ruminal de genótipos de cana-de-açúcar cultivados em regime de sequeiro - LEITE , Marcos Renan Lima (2018)
The present study had as objective to evaluate the agronomic, chemical characteristics and ruminal degradability of 15 genotypes of sugarcane (CV-4, RB-002504, RB-002754, RB- 041443, RB-855035, RB-863129, RB-867515, RB-92579, RB-931011, RB-951541, RB- 962962, RB-992506, RB-99395, SP-813250 and VAT-90212) cultivated under rain fed conditions, for use in feeding dairy cattle. The experiment was designed in a randomized block design with three replicates, totaling 45 experimental plots. The biometric analyzes were performed at 240, 360 and 510 days after planting (DAP), where they were evaluated: plant length (PL), stalk length (SL), stalk diameter (SD), leaf area (LA) and number of green leaves (NGL). In the last data collection (510 DAP), the evaluations were made plant weight (PW), stalk weight (SW) number internodes (NI), tons of stalk per hectare (TSH), tons of matter dry per hectare (TDMH) and Brix. Stalk samples of each genotype were harvested in forage and pre-dried in a forced ventilation oven at 60ºC for 72 hours for analysis of the chemical composition: dry matter (DM), mineral matter (MM), neutral detergent fiber (NDF) acid detergent fiber (ADF), cellulose (Cel), hemicellulose (Hem) and lignin (Lig). For analysis of the in situ ruminal degradability of 24 hours of dry matter and neutral detergent fiber, were used three Girolando cannulated heifers with a mean weight of 390±10kg. Samples containing 5 g of pre-dried matter from the stalks were weighed into 100-gram non-woven fabric (NWF) sachets and incubated in the rumen. The ruminal DM degradability was calculated with the disappearance of DM in 24 hours of incubation, in proportion to the originally incubated MS, and the dry matter residue was calculated after 72 h of incubation (RES 72). The percentage of NDF was determined in the ruminal incubation residues and the degradation of NDF was calculated. The data were submitted to statistical analysis. The cane genotypes RB- 867515, CV-4, RB-951541, RB-92579 and RB-041443 are best indicated for use in the dairy cattle diet, due to higher shoot productivity, brix values and degradability of DM and FDN. The cane genotypes RB-99395, RB-992506, SP-813250, RB-002754 and RB-0025004 are not indicated for cultivation under the conditions of the present study, as a function of the susceptibility to water deficit in its initial stages of growth.